Evaluation of cowpea genotypes for field resistance to the legume pod borer, M. testulalis in Nigeria - Oghiakhe, S.; Jackai, L.E.N.; Makanjuola, W.A. (Elsevier, 1995)
Eighteen cowpea cultivars were screened for resistance to the legume pod borer, Maruca testulalis under field conditions at two locations (Mokwa and Ibadan) in Nigeria under unprotected and two types of insecticide protection levels. Unprotected plots gave zero yield due to their exposure to the entire cowpea pest complex. Plots that received a mixture of Cypermethrin and dimethoate (as Cymbush Super ED®) treatment were better (P < 0.05) than plots treated with monocrotophos (as Nuvacron 40EC) in all the damage parameters studied. Results showed that larval population per se are not adequate in resistance categorization of cowpea cultivars. For percentage pod damage at both locations, TVu 946, MRx2-84F and MRx109-84F were the best three cultivars while IT82D-716 was the worst. Yield reduction caused by M. testulalis at Ibadan ranged from 3.47% in MRx2-84F to 49.75% in IT82D-716; at Mokwa values ranged from 10.65% for MRx54-84M to 52.23% for MRx15-84F. Based on their yield performance, among other resistance parameters, the following eight cultivars were selected as moderately resistant to M. testulalis: MRx2-84F, MRx49-84M, MRx109-84M, MRx50-84M, MRx54-84M, MRx55-84M, MRx8-84F and MRx48-84M. These cultivars have good plant type and are either white or brown seeded which makes them good candidates that could be used in breeding programme.